Development of a nucleic acid-based monoclonal antibody technique for the detection of the bacterial wilt organism in banana in the Philippines - Exconde, Severina B.; Raymundo, Asuncion K.; Espino, Teresita M. (2000)
A method for detecting the bacterial wilt organism, Ralstonia solanacearum, in banana was developed. This was based on monoclonal antibodies (MABs) generated using a polymerase chain reaction (PCR) product, M114, for enhanced specificity. The DNA fragment plus methylated bovine serum albumin (MBSA) was used as immunogen in contrast to the conventional method utilizing whole bacterial cells or other bacterial antigens in producing antibodies for the detection of a plant pathogen. Two of the five monoclones produced were the source of the MAB. The activity and specificity of the developed MAB were confirmed through cross reactivity tests against 12 different genera of bacterial pathogens, 10 species of Pseudomonas, and banana and non-banana isolates. None of the tested bacterial genera cross-reacted with the developed MAB and only one species of Pseudomonas, P. maltophilia, showed cross reaction with the antibody. However, no PCR amplification in its DNA using M114 primers was observed in this species. Some tomato strains that were established to also infect bananas cross-reacted with the produced antibody. In the sensitivity tests of produced banana monoclonal antibodies, the detection limit for whole cells in culture and in soil was 1 × 107 cells mL-1 and for lysed cells 1 × 105 cells mL-1.
Keywords: Bacterial wilt diseases; Banana diseases and pests; Philippine bananas